A comparison on Industry 4.0 and Lean Production between manufacturers from emerging and developed economies. (18th August 2021) - Tortorella, Guilherme Luz; Rossini, Matteo; Costa, Federica; Portioli Staudacher, Alberto; Sawhney, Rapinder
Abstract : This study examines the differences in implementation level of both Industry 4.0 (I4.0) and Lean Production (LP), whose integration is denoted here as Lean Automation (LA), between manufacturers located in emerging and developed economies. A survey-based research was carried out with a total of 249 Brazilian (emerging economy) and Italian (developed economy) companies that are implementing LP and have initiated the adoption of I4.0 technologies. Collected data was analysed through multivariate data techniques. Results indicate that the socio-economic context where companies are located does influence the extension of LA implementation. However, they also suggest that, if properly managed, a high level of LA implementation is feasible regardless the socio-economic barriers and challenges that manufacturers may face. Further, companies' characteristics that favour higher LA levels might also vary between emerging and developed economies, emphasising the importance of a clear understanding of the socio-economic specificities of the contexts. This study sheds light on how pervasive LA implementation can be in manufacturers from both socio-economic contexts. Moreover, these outcomes demystify assumptions related to management approaches that may only prevail if certain socio-economic conditions are present. This evidence is especially important for multinational companies that seek for highly competitive standards across all their sites.